1996
DOI: 10.1093/brain/119.3.741
|View full text |Cite
|
Sign up to set email alerts
|

Auditory neuropathy

Abstract: Ten patients presented as children or young adults with hearing impairments that, by behavioural and physiological testing, were compatible with a disorder of the auditory portion of the VIII cranial nerve. Evidence of normal cochlear outer hair cell function was provided by preservation of otoacoustic emissions and cochlear microphonics in all of the patients. Auditory brainstem potentials showed evidence of abnormal auditory pathway function beginning with the VIII nerve: the potentials were absent in nine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
864
4
74

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 1,013 publications
(973 citation statements)
references
References 0 publications
31
864
4
74
Order By: Relevance
“…5 and 6) and the 20-to 30-dB mismatch between ABR and DPOAE threshold shifts (Fig. 1) suggest that disruption of the SLC19A2 gene may underlie some forms of Bauditory neuropathy,^a clinical diagnosis characterized by persistence of measurable OAEs in cases with profound reduction in ABRs (Starr et al 1996). Although DPOAEs were slightly reduced in our transporter-null mice (Fig.…”
Section: Figmentioning
confidence: 67%
“…5 and 6) and the 20-to 30-dB mismatch between ABR and DPOAE threshold shifts (Fig. 1) suggest that disruption of the SLC19A2 gene may underlie some forms of Bauditory neuropathy,^a clinical diagnosis characterized by persistence of measurable OAEs in cases with profound reduction in ABRs (Starr et al 1996). Although DPOAEs were slightly reduced in our transporter-null mice (Fig.…”
Section: Figmentioning
confidence: 67%
“…The clinical condition known as AN, defined as a hearing impairment seen with absent ABRs despite present OAEs (Starr et al 1996), clearly has several underlying etiologies, including both genetic and acquired. The maintenance of OAEs indicates (1) that the middle ear must be normal or near normal and (2) that basic cochlear architecture must be intact, including the stria vascularis, to produce an endolymphatic potential and the OHCs to drive the cochlear amplifier (Shera 2004).…”
Section: Selective Ihc Loss Prematurity and Auditory Neuropathymentioning
confidence: 99%
“…Comparison of results from these two tests has revealed that a subset of sensorineural hearing impairments arise despite apparently normal function of the outer hair cells, as implied by intact OAE responses despite absent or greatly attenuated ABRs. This clinical condition has been termed auditory neuropathy (AN;Starr et al 1996Starr et al , 2000, even though it could logically arise from either damage/degeneration of the cochlear nerve or selective damage/degeneration of the inner hair cells, which provide the exclusive synaptic drive to 95% of the cochlear nerve fibers (Spoendlin 1972). Depending on the size and nature of the population sampled, estimates of the prevalence of AN range anywhere from 5% to 15% of those with sensorineural hearing loss (Rance et al 1999;D'Agostino and Austin 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Auditory brainstem responses (ABRs) are the predominant clinical measure of objec-tively determining hearing thresholds (Hood 1990;Starr et al 1996;Thompson et al 2001). Wave amplitudes measured from ABRs also provide insight into the representation of phasic information to short stimuli, based on clearly defined peaks that have been mapped onto specific generators in the auditory brainstem and midbrain (Lev and Sohmer 1972;Rowe 1981;Chen and Chen 1991).…”
Section: Introductionmentioning
confidence: 99%